Model of interprofessional care for the newborn and family during neonatal death and dying: a multistage evaluation mixed methods study. - da Rosa, Rosiane; dos Santos, José Luís Guedes; Ross, Ratchneewan; de Lima, Margarete Maria; Antunes Wilhelm, Laís; Costa, Roberta (Journal of Interprofessional Care)
An interprofessional care model is crucial to advancing the quality of integrated, patient-centered care, particularly in critical situations. The purpose of this study was to develop an interprofessional care model for newborns and their families experiencing neonatal death and dying. This is an explanatory sequential mixed-methods design with three phases. Data were collected in two public neonatal units in Brazil. In Phase I, quantitative data were collected from 66 healthcare professionals using two instruments: demographic characterization and the Profile of Attitudes Toward Death – Brazilian version. In Phase II, qualitative data were collected and analyzed using Grounded Theory with 13 professionals. Phase III evaluated the proposed model. The model emphasizes sensitive and holistic care, tailored to the needs of newborns and families experiencing neonatal death and dying. It emphasizes adequate training for the healthcare team, along with a strong support network, solid teamwork, a supportive environment, clear and positive interprofessional and professional-family communication, time reserved for parents with the newborn, and a time to say goodbye. The model was evaluated as suitable for guiding interprofessional teams in the context of neonatal death and dying, with a Content Validity Index (CCI) above 80% in all categories. Although communication and family support are pillars of palliative care, the model proposed in this study stands out for its systematic approach to integrating team support, recognizing that the attitude and well-being of professionals are crucial to the provision of sensitive and holistic interprofessional care. Future research should apply, test, and adjust the model in real neonatal settings.